(untitled) (Open Herald: Periodical of Methodical Research, 2024)
A family of viruses known as coronaviruses is responsible for illnesses like the common cold, Middle East respiratory syndrome (MERS), and severe acute respiratory syndrome (SARS). 2019 saw the discovery of a novel coronavirus that was responsible for an outbreak of a disease with Chinese origins.The virus is referred to as SARS-CoV-2, or severe acute respiratory syndrome coronavirus. Novel coronavirus disease 2019 (COVID-19) is the name given to the ensuing illness. The World Health Organization proclaimed the coronavirus (COVID-19) to be a worldwide pandemic in March 2020. The current study was conducted in the laboratories of the Faculty of Science Sumer University. We collected 100 blood samples from students of the Faculty of Science 53 males and 47 females who had taken corona vaccines, such as the Pfizer and AstraZeneca vaccines. The time of collecting samples was in January 2022 after they had taken the last dose of vaccines. The current study aimed to find out whether the different corona vaccines have an effect on the appearance of rheumatoid factor in the serum of the study sample students. Where the results were compared with a control sample of 100 apparently healthy people who were not vaccinated with Corona vaccines. The current results showed that all students did not have rheumatoid factor, meaning that the test result was negative. Therefore, it is possible, through this study, to conclude, at the level of the sample taken, that there is no effect of the vaccines used for the Corona virus on the appearance of the rheumatoid factor.